1990
DOI: 10.1143/jjap.29.611
|View full text |Cite
|
Sign up to set email alerts
|

Wavenumber Measurement of the 1.5-µm Band of Acetylene by Semiconductor Laser Spectrometer

Abstract: Near-infrared distributed feedback (DFB) semiconductor laser spectroscopy of acetylene has been carried out from 6450 to 6570 cm-1 with an accuracy of about 0.0033 cm-1. The molecular constants of the (1010000)–(0000000), (1011100)–(0001100), and (1010011)–(0000011) bands of 12C2H2 and the (1010000)–(0000000) and (0020000)–(0000000) bands of 12C13CH2 have been precisely determined. The transition frequencies calculated from the constants can be used as references for optical communication systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…As can be seen, the values of the constants we obtain are in good agreement with previously published values obtained using FTIR spectroscopy [14] whilst having much improved precision. The agreement with previously published values obtained using laser spectroscopy [2,13] is also reasonably good, bearing in mind their estimated experimental uncertainties of 150 kHz and 100 MHz, respectively. The constants published here reproduce the experimentally observed wavenumbers for lines R (10) to R (18) given in [2] to within the quoted experimental uncertainty.…”
Section: Results and Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…As can be seen, the values of the constants we obtain are in good agreement with previously published values obtained using FTIR spectroscopy [14] whilst having much improved precision. The agreement with previously published values obtained using laser spectroscopy [2,13] is also reasonably good, bearing in mind their estimated experimental uncertainties of 150 kHz and 100 MHz, respectively. The constants published here reproduce the experimentally observed wavenumbers for lines R (10) to R (18) given in [2] to within the quoted experimental uncertainty.…”
Section: Results and Analysissupporting
confidence: 89%
“…Thus, if one of the two acetylene transition frequencies f ref is known, along with the comb mode order number n, and the sign of f beat and f synth , the unknown acetylene frequency f meas is given by f meas = f ref + nf m + f synth + f count . The starting frequencies for f ref were 13 C 2 H 2 transitions measured using a combination of frequency chain, femtosecond comb, and OFCG [9]. A pair of measurements were made of each line, with NPL-ECL2 locked to a reference line and NPL-ECL1 locked to a 12 C 2 H 2 line of unknown frequency, and then with the roles swapped.…”
Section: Frequency Metrology With the Optical Frequency Comb Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…The combination band ν 2 + ν 3 + ν 4 + ν 5 (ν 2 is the C≡C stretching vibrational mode) has also been observed tentatively before (4), although about 10 cm −1 higher than what we have. Although our results are generally in good agreement with the earlier diode laser study (9), they are clearly more precise, as indicated by our smaller standard deviations and better determined rotational parameters. However, there is a small 0.009 cm −1 deviation in the value of the vibrational origin energy of the dominating ν 1 + ν 3 band which cannot necessarily be explained by the experimental accuracy of the measurements.…”
Section: Resultssupporting
confidence: 90%
“…The second C-H stretching overtone region has not been studied at high resolution. The subject of this work, the first overtone band system at about 6500 cm −1 , was previously recorded with an enriched 13 C sample using a grating spectrometer (4) and later with a natural acetylene sample using a semiconductor laser spectrometer (9). In this study, we have extended those works with enhanced resolution and signal-to-noise ratio.…”
Section: Introductionmentioning
confidence: 93%